2020
DOI: 10.3390/s20185122
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition of Cognitive Load Using EEG and ECG Signals

Abstract: The matching of cognitive load and working memory is the key for effective learning, and cognitive effort in the learning process has nervous responses which can be quantified in various physiological parameters. Therefore, it is meaningful to explore automatic cognitive load pattern recognition by using physiological measures. Firstly, this work extracted 33 commonly used physiological features to quantify autonomic and central nervous activities. Secondly, we selected a critical feature subset for cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…We used eight algorithms based on feature selection to classify the datasets, which included K-nearest neighbor (KNN), neural network (NN), linear discriminant analysis (LDA) [ 40 ], logistic regression (LR) [ 41 ], random forest (RF) [ 27 , 41 , 42 ], decision tree (DT) [ 42 , 43 ], support vector machines (SVM) [ 23 ] and gradient boost decision tree (GBDT). All algorithms were implemented with Python sklearn library.…”
Section: Resultsmentioning
confidence: 99%
“…We used eight algorithms based on feature selection to classify the datasets, which included K-nearest neighbor (KNN), neural network (NN), linear discriminant analysis (LDA) [ 40 ], logistic regression (LR) [ 41 ], random forest (RF) [ 27 , 41 , 42 ], decision tree (DT) [ 42 , 43 ], support vector machines (SVM) [ 23 ] and gradient boost decision tree (GBDT). All algorithms were implemented with Python sklearn library.…”
Section: Resultsmentioning
confidence: 99%
“…Classification algorithms include classifying between discrete MWL states (i.e., resting, low and high) with the use of ML models, such as Artificial Neural Networks (ANN) [47,48], Support Vector Machines (SVM) [38,49] or Linear Discriminant Analysis (LDA) [19,41] (or extended variants). In addition to this, some studies compare several classification models when performing MWL estimations [50,51]. The use of regression models, such as Neuro Fuzzy Systems (NFS) [46,52,53] and Gaussian process regression [44], provides a continuous estimation of MWL but is less reported.…”
Section: Multimodal Fusion For Inferring Mwlmentioning
confidence: 99%
“…Whereas studies by Zhang et al and Wang et al [46,58,59] demonstrated large time intervals, Lim et al [52] lacked the ability to demonstrate an inference of MWL during an online validation. Moreover, recent studies have outlined the importance of investigating the features contributing to the performance of the respective model used [50,51]. This is also an area that was not investigated for NFS in previous studies.…”
Section: Multimodal Fusion For Inferring Mwlmentioning
confidence: 99%
“…Moreover, the multivariate pattern analysis method can discover potential biomarkers based on multimodal physiological signals to distinguish patients from normal controls at the individual level and further highlight the physiological mechanism of PD behavioral symptoms. Recently, many researchers combine multimodal physiological data with machine learning methods and have obtained many valuable results [15][16][17][18]. Kyle Ross et al used ECG and galvanic skin response (GSR) signals to classify professional trauma patients and novices at a professional level and achieved an accuracy of 79.84% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Kyle Ross et al used ECG and galvanic skin response (GSR) signals to classify professional trauma patients and novices at a professional level and achieved an accuracy of 79.84% [15]. Rong L et al used EEG and ECG signals combined with the SVM model to classify cognitive load, which yielded an accuracy of 97.2% [16]. Sara et al used electromyogram (EMG) and ECG data combined with feature selection and machine learning algorithms to detect the psychological stress of healthy people, and the four levels of pressure recognition accuracy reached 96.2% [17].…”
Section: Introductionmentioning
confidence: 99%